BUILDING ACADEMIC STAFF CAPACITY TO SUPPORT ONLINE LEARNING IN DEVELOPING COUNTRIES - Greig Krull; Brenda Mallinson (Online Learning, 2013)
Higher Education Institutions (HEIs) in Africa face the challenge of responding to the expanding demand for tertiary education while maintaining or enhancing the quality of their course offerings. This has led to some HEIs introducing interactive web technologies to support their distance teaching and learning practices. However, academic staff at these institutions may struggle to provide sufficient support to online learners in part due to inadequate staff capacity in terms of familiarity with and use of online communication tools. This paper reports the practical experiences of building academic staff capacity within three southern Africa institutions, in order to initiate skills development and introduce foundational concepts in support of engaging online learners. The design of the course material is discussed and the experiences of the facilitators and participants are examined.